Sinocrassula holotricha (Crassulaceae), a new species from Sichuan, China - Zhi-Bai Xu; Jing Zhao; Rong-Juan Li; Hong Jiang; Jia-Guan Wang; Chao Chen (PhytoKeys)
A new species of crassulacean acid metabolism, Sinocrassula holotricha, is described based on specimen collected from Sichuan Province, Southwest China. The new species can be distinguished from its morphologically and phylogenetically related species by the hairy plants and lack of rosette. In the present study, a molecular phylogeny, taxonomic description, distribution information, and photographs of this new species are presented.